Pemberdayaan UMKM oleh Dinas Koperasi Usaha Kecil Menengah Perindustrian dan Perdagangan Kabupaten Pelalawan - Melsa Ranika; Mayarni Mayarni (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
Micro, Small and Medium Enterprises (MSMEs) have a crucial role in the economic dynamics of a region. MSMEs are not only a source of job creation, but also have great potential to encourage inclusive economic growth. Empowering MSMEs is a strategic key to optimizing the contribution of MSMEs to the economy. This involves various efforts, such as education and training to improve the skills of MSME entrepreneurs, easier access to financial resources, and support in marketing and product promotion. There are obstacles in empowering MSMEs in Pelalawan Regency, namely that the Human Resources (HR) owned by the department are inadequate, so they are less effective in empowering MSMEs in Pelalawan Regency. Lack of government budget to empower MSMEs. The aim of this research is to find out how the Department of Cooperatives, SMEs, Industry and Trade attempts to empower MSMEs in Pelalawan Regency. The theory used is the Stages of Empowerment by Ambar firm. S. (2013:162). The research method uses qualitative methods with a descriptive approach. The results of this research are the Department of Cooperatives, SMEs, Industry and Trade, Kab. Pelalawan has made efforts in several aspects, community empowerment, but it is still not optimal. The research recommendation is that it is hoped that empowerment parties will be more active and more innovative in the future to maintain this empowerment achievement.